Complete coding sequences of five dengue virus type 2 clinical isolates from Venezuela obtained through shotgun metagenomics - Lizarazo, Erley; Couto, Natacha; Vincenti-Gonzalez, Maria; Raangs, Erwin C.; Jänisch, Thomas; Friedrich, Alex W.; Tami, Adriana; Rossen, John W. (Genome announcements, 2018)
Dengue is a disease endemic in Latin American countries, like Venezuela, and has become one of the most important public health problems. We report five complete coding sequences of dengue virus serotype 2 (DENV-2) isolated from DENV-infected patients in Venezuela. Phylogenetic analysis placed the isolates within the American/Asian genotype.
Gesehen am 26.02.2020